The Stratigraphy and Lithology of the Kuma River area Buru Island, Maluku - H.Harahap, Bhakti; Poedjoprajitno, Soemantri (Pusat Survei Geologi, 2006)
The stratigraphy of Kuma River area is divided into six formations, bottom to top, Dalan, Duna, Kuma, Waeken, Wakatin, and Leko Conglomerate. The Dalan Formation is Trassic in age composed of interbedded well-bedded claystone and sandstone with a typical turbidite sequences. The Duna Formation is Jurassic in age, consisting of interbedded pelagic limestone and fossil (ammonites and belemnites) rich beds. The Kuma Formation is Upper Cretaceous to Eocene age comprising well-bedded medium beds pelagic limestone with abundant planktonic forams. The Waeken is Oligocene- Miocene age and comprises micaceous mudstone. The Wakatin Formation consists of light gray massive reefal limestone containing corals, sponge, algae, bivalves and benthonic foraminifers. The Leko Formation has a Pleistocene age consisting of conglomerate. Structural geology of this area comprises anticline, syncline, and normal fault that relats to the block faulting. The presence of reservoir and source rocks and also fold structure may play an important role in hydrocarbon prospective of the area. Keywords: interbedded pelagic limestone, turbidite sequences, chert layers, hydrocarbon